Whose Land Is It Anyway?: A Manual for Decolonization - McFarlane, Peter; Schabus, Nicole (Fédération of Post-Secondary Education of BC, 2018)
Whose Land Is It Anyway? A Manual for Decolonization provides a variety of Indigenous perspectives on the history of colonialism, current Indigenous activism and resistance, and outlines the path forward to reconciliation. This audio version features renowned Indigenous writers Taiaiake Alfred, Glen Coulthard, Russell Diabo, Beverly Jacobs, Melina Laboucan-Massimo, Kanahus Manuel, Jeffrey McNeil-Seymour, Pamela Palmater, Shiri Pasternak, Nicole Schabus, Senator Murray Sinclair, and Sharon Venne. The late Arthur Manuel’s writings are read by his grandson, Mahekan Anderson.
OCLC: 1122613551
Keywords: 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé